Does Political Party Affiliation Moderate the Effects of Exposure to Claims of Discrimination? - Rasmussen, Raea. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Psychology.; Advisor: Samuel Sommers.; Committee: Keith Maddox, Jessica Remedios, and Mary Murphy.; Keyword: Social psychology.